Bridging and bonding: having a Muslim diversity on corporate boards and firm performance - Hassan, R. (Emerald Group Publishing Ltd., 2018)
Purpose: This paper aims to examine the demographic diversity at top-level management and its impact on the performance of Malaysian-listed companies. In addition, Muslim diversity on corporate boards is examined. Design/methodology/approach: Although many organisations aspire to be socially diverse, diversityâs consequences for organisational performance remain unclear. This study specifies the whole distinct mechanism and measures it independently, bridging as the demographic diversity among the board of directors (BODs) and bonding as the firmâs financial performance. To maintain the homogeneity factor, the empirical analysis has been confined to 12 fully fledged sectors and 529 Malaysian listed firms out of 798 firms selected on the basis of judgmental sampling during the period of 2013. The paper applies the correlation matrix and linear regression model to justify this phenomenon. Findings: The empirical findings suggest that gender diversity (Muslim and Non-Muslim women) is positively significant with firm performance with regards to management, shareholders and market perspectives. It means that both Muslim and non-Muslim women are contributing to firm performance. Ethnic diversity (minority) and Muslim diversity (majority) have no impact on firm performance. On the other hand, interaction variables are positively significant with firm performance. It means that majority and minorities are essential for corporate boards to produce a greater performance. Research limitations/implications: Future research could include more variables such as directorâs age profile and foreign participation as well as other types of diversities, such as cognitive diversity and corporate diversity. In addition, another possible extension could be the investigation of diversity issues between small scale and large or high and low-profit firms. The findings provide insightful information to firms, as this study suggests that the diverse corporate boards can enhance firm performance. Originality/value: In recent years, diversity issues have been examined with regard to firm performance of the listed companies. Whilst extensive literature exists on diversity issues, this issue is still under debate and has had inconsistent results. The paper attempts to fill the gap in the existing literature, discuss the empirically diverse corporate boards with the interaction approach and impact on the firm performance. Â© 2018, Emerald Publishing Limited.